Shifting Focus: Collecting Focus Group Data Online - Anissa Zagonel; Audrey King; Lauri M. Baker; Angela B. Lindsey; Sandra Anderson; Ricky W. Telg; Ashley McLeod-Morin (EDIS)
This new 5-page publication of the UF/IFAS Department of Agricultural Education and Communication presents what focus groups are, the differences between in-person and online focus groups, potential platforms for hosting online focus groups, advantages and disadvantages to online focus groups, and best practices for conducting your own online focus groups. Researchers and practitioners alike can use this document to guide their process of conducting online focus groups. This article only discusses conducting online focus groups through online videoconferencing software. https://edis.ifas.ufl.edu/wc413